Morphological and physiologо- biochemical parameters of stability to a drought Triticum aestivum L. (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The review of a problem stability to a drought of plants wheat and phenomena connected to it on molecular, subcellular, cellular, tissue, оrgan and оrganism levels; the examples of artificial populations (varieties) wheat are given, which have the genetically determined features stability to a drought, the mechanisms and directions of researches of adaptive features of plants wheat to deficiency of a moisture (drought) and raised temperatures are opened.
Keywords: morphotype, stability to a drought, sort Triticum, mikrostructure, metabolism.